Book Review: The Wiley Blackwell Companion to Religion and Peace (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
Book Review of Jolyon Mitchell, Suzanna R. Millar, Francesca Po, and Martyn Percy, eds., The Wiley Blackwell Companion to Religion and Peace, The Wiley Blackwell Companions to Religion series, Wiley Blackwell, 2022, 656 pp., €152.60 (Hardcover), ISBN: 978-1-119-42434-5.
Keywords: Religion; Peace; Religion and Peace